Soil Water Availability Changes in Amount and Timing Favor the Growth and Competitiveness of Grass Than a Co-dominant Legume in Their Mixtures - Xu, Weizhou; Deng, Xiping; Xu, Bingcheng; Palta, Jairo A.; Chen, Yinglong (Frontiers in Plant Science, 2021)
The grasslands on the semi-arid Loess Plateau of China are expected to be particularly responsive to the size and frequency changes of extreme precipitation events because their ecological processes are largely driven by distinct soil moisture pulses. However, the plant growth and competitiveness of co-dominant species in response to the changes in the amount and timing of soil water are still unclear. Thus, two co-dominant species, Bothriochloa ischaemum and Lespedeza davurica, were grown in seven mixture ratios under three watering regimes [80 ± 5% pot soil capacity (FC) (high watering), 60 ± 5% FC (moderate watering), and 40 ± 5% FC (low watering)] in a pot experiment. The soil water contents were rapidly improved from low to moderate water and from moderate to high water, respectively, at the heading, flowering, and maturity stages of B. ischaemum, and were maintained until the end of the growing season of each species. The biomass production of both species increased significantly with the increased soil water contents, particularly at the heading and flowering periods, with a more pronounced increase in B. ischaemum in the mixtures. The root/shoot ratio of both species was decreased when the soil water availability increased at the heading or flowering periods. The total biomass production, water use efficiency (WUE), and relative yield total (RYT) increased gradually with the increase of B. ischaemum in the mixtures. The relative competition intensity was below zero in B. ischaemum, and above zero in L. davurica. The competitive balance index calculated for B. ischaemum was increased with the increase of the soil water contents. Bothriochloa ischaemum responded more positively to the periodical increase in soil water availability than L. davurica, indicating that the abundance of B. ischaemum could increase in relatively wet seasons or plenty-rainfall periods. In addition, the mixture ratio of 10:2 (B. ischaemum to L. davurica) was the most compatible combination for the improved biomass production, WUE, and RYTs across all soil water treatments.